Distribution of epi-endogeic and endogeic earthworm species (Oligochaeta: Lumbricidae) in the forest belt of the Northwest Caucasus - Geraskina, Anna; Shevchenko, Nikolay (Zootaxa, 2021)
The distribution of the often dominant in density and biomass epi-endogeic and endogeic earthworm species in forests of the Northwest Caucasus was estimated based on a large array of field data and GIS modeling of modern potential areas. Quantitative accountings of earthworms were conducted annually from 2014 to 2019 in different types of forests: sticky alder forest, small-leaved forests, broadleaf forests (hornbeam and beech forests), coniferous-deciduous forests, dark coniferous forests, and pine forests (792 geographic locations). It is shown that the native species of the Caucasian fauna dominate in the number and biomass from piedmont to high mountain forests. The most widespread species that is found in all types of forests from low to high mountains and makes the main contribution to the biomass of earthworms is the Crimean-Caucasian subendemic Dendrobaena schmidti. Peregrine species of epi-endogeic and endogeic earthworms inhabit sticky alder forest, small-leaved, broadleaf and pine forests in which they inhabit together with native species, while not dominating either in numbers or in biomass among other species. Dark coniferous forests are inhabited mainly by the native endogeic species D. schmidti and A. jassyensis. Maxent modeling shows that the species of the endogeic earthworm group have wider potential areas than epi-endogeic species. The most significant bioclimatic factors that make the greatest contribution to the distribution: amount of precipitation in the driest month, altitude above the sea level, isothermality.